Relationship of Knowledge and Attitudes of Princess Adolescent About Breast Cancer with an Examination of Early Detection in SMA Khatolik Kabanjahe Districts Kabanjahe Karo Regency 2019 - Jenny Sembiring Meliala (Institute of Computer Science (IOCS), 2020)
Breast cancer is cancer of a malignant tumor of the breast. Millions of women die from breast cancer. Each year of the 250,000 new cases of breast cancer diagnosed in Europe and 175,000 in the United States, about 50% of patients diagnosed with breast cancer are at a late stage and survive only 18-30 months. Early detection can be suppressing. the mortality rate is 25-30%. The purpose of this study was to determine the relationship between knowledge of young women about breast cancer and early detection, where breast cancer can be found early with BSE examination. The type of research used is cross sectional, where the population is all female teenagers in SMA Khatolik Kabanjahe in 2019 with a total of 110 respondents. The sample size is 52 respondents through Systematic Random Sampling. The statistical test used is the statistical test Chi-Square = 0.05. The results of the analysis showed that the majority of young women who had good knowledge did early detection checks, 19%, those who had sufficient knowledge, the majority also did early detection checks, 81%, the majority did not perform early detection checks, 71%. who have a positive attitude, the majority do 100% early detection checks. And those who have a negative attitude majority do not perform early detection checks 84% ​​The results of the Chi-Square test have a relationship between the knowledge of young women about breast cancer with early detection examinations with p = 0.000, and there is a relationship between the attitudes of young women about breast cancer and early detection tests = 0,000. It is hoped that young women at Khatolik Kabanjahe Senior High School,